Komparasi Arah Kiblat: Masjid Kuno Songak dan Majis Kuno Bayan di Lombok - Utami, Tri Pangestu; Awaludin, Muhammad (Universitas Islam Negeri Mataram, 2021)
The Songak ancient mosque and the Bayan ancient mosque are two historic ancient mosques on Lombok island. The two mosques are also witnesses to the history of the spread of Islam in Lombok, so the two mosques are still being maintained and preserved to this day. Besides being a place of worship, the mosques also serve as a place to celebrate Islamic holidays and the culture of the local community. Therefore, it is very important to check the Qibla direction of the two ancient mosques, because one of the conditions for a valid prayer is facing the Qibla. This study produces data that there is a deviation from the Qibla direction in the two historic ancient mosques. The Bayan ancient mosque is considered to have a smaller deviation than the Songak ancient mosque. Masjid kuno Songak dan masjid kuno Bayan merupakan dua masjid kuno bersejarah di pulau lombok. Masjid tersebut juga merupakan saksi sejarah penyebaran islam di lombok, sehingga kedua masjid tersebut masih terus dipelihara dan dipertahanan hingga saat ini. Selain sebagai tempat ibadah, kedua masjid tersebut juga dijadikan sebagai tempat perayaan hari besar islam dan kebudayaan masyarakat setempat. Oleh karena itu, pengecekan arah kiblat kedua masjid kuno tersebut sangat penting untuk dilakukan, sebab salah satu syarat sah sholat adalah menghadap kiblat. Penelitian ini menghasilkan data bahwa adanya kemelencengan arah kiblat pada kedua masjid kuno bersejarah tersebut. Masjid kuno Bayan dianggap memiliki kemelencengan yang lebih kecil dibanding dengan masjid kuno Songak.